PENDIDIKAN ISLAM DALAM FENOMENA DISRUPTION 4.0 - Hair, Moh Afiful; Subhan, Moh (AHSANA MEDIA: Jurnal Pemikiran, Pendidikan dan Penelitian Ke-Islaman, 2019)
Massivereform in thebodyofIslamic education. Thisreformis necessaryforIslamiceducationtorespondtothechallengesand demandsofthechangingage.Inaddition,,theeraof4.0has a broadimpactinallareasoflife,notleastinthefieldofeducation.Theerathatgavebirthto thisphenomenon disruptionrequires the Islamic educationworld toparticipatein adjusting. Islamiceducationgraduatesarenow facedwithnewchallenges,demands,andneedsthathave neverexisted before. So it is necessary toupdate and innovatethesystem,governance, curriculum,competence ofhumanresources, facilitiesand infrastructure,culture,work ethic, andothers.Otherwise,Islamiceducationwillbeincreasinglylaggingandobsolete.Therefore, it is necessary to finddefinite steps forIslamic education inorder to remain competitive in this disruption era. Solutive step isto participate disruption themselves.